Recents developments in cowpea germplasm collection, conservation, evaluation and research at the Genetic Resources Unit - Ng, N.Q. (1990)
The history of the Genetic Resources Unit at the International Institute of Tropical Agriculture (IITA) was highlighted. By 1980, the unit engaged in characterization and evaluation of germplasm information. In order to strengthen the units activity and provide a better knowledge of Vigna, the government of Italy funded a project from December 1984 to December 1989. Information on the geographical distribution of Vigna were also given. The unit now maintains 923 accessions of wild vigna species and about 15,200 accessions of cultivated cowpea.